Good governance and confidentiality: a matter of the preservation of the public sphere. Issue 4 (29th July 2014) - Goede, Miguel; J. Neuwirth, Rostam
Abstract : Purpose: – The purpose of this article is to discuss the concepts confidentiality and transparency in the context of good governance. Design/methodology/approach: – After exploring the concepts of confidentiality, good governance and other relevant concepts, they are related to each other. Findings: – When it comes to good governance, transparency is overrated and confidentiality is taken for granted. For good governance, there must be a balance between the two to preserve the public sphere. Originality/value: – The paper contributes to the understanding of good governance and the evolution of the public sphere.